2016
DOI: 10.1111/1462-2920.13498
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum

Abstract: Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum, acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen-rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…Detection and measurement of GA and its mesostate in the GA biosynthesis pathway. GAs, squalene, and lanosterol were extracted and measured from fungal mycelia according to a previously described method (37). Ganoderic acid-a was used as the standard (38).…”
Section: Methodsmentioning
confidence: 99%
“…Detection and measurement of GA and its mesostate in the GA biosynthesis pathway. GAs, squalene, and lanosterol were extracted and measured from fungal mycelia according to a previously described method (37). Ganoderic acid-a was used as the standard (38).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, enhancing the content of GA is important and urgently needed to be solved. The growth of G. lucidum and the synthesis of SMs are affected by a variety of environmental factors, such as nutrients, chemical inducement and physical stresses (Shi et al, 2015;Liu et al, 2017;Ren et al, 2017;Liu et al, 2018a). Among these factors, nitrogen plays a special role in the biosynthesis of SMs, and changes of nitrogen sources or the C/N ratio could result in an enhancement of GA (Hsieh and Yang, 2004;Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing GSH and thioredoxin pool in cancer cells, through the inhibition of GR and TrxR enzymes, may be considered as an effective strategy to combat these tumor cells by altering their ability to eliminate ROS and to cope with oxidative damage. Both glutathioneand thioredoxin-dependent systems require NADPH, as cofactor, to combat ROS generated from oxidative stress [9]. It has been systematically showed that NADPH is a limiting factor for oxidative stress management in cancer cells.…”
Section: Introductionmentioning
confidence: 99%